Thalers and „ephimek” coin with marks in the collection of the National Museum of History and Ethnography „Perejaslav”, as a source for learning about the circulation of currency in the Ukraine in the 16th-18th centuries - Коцур, Виктор (Acta Archaeologica Lodziensia, 2018)
Thalers struck by Central European rulers were in circulation in the Eastern part of Europe too. Among the numismatic holdings of the “Pereyaslav” National Museum in Ukraine are coins of this type, which were in circulation throughout Ukrainian territory. The present publication of the Museum holdings of coins of this type supplements our picture of coin circulation in Ukraine in the 17th and 18th centuries.